APA KENDALA MAHASISWA OLAHRAGA YANG TIDAK MAHIR BERENANG ? - Haryanto, Arief Ibnu; Pulungan, Khoirul Anwar; Siregar, Nurkhoiroh; Kadir, Sulasikin Sahdi; Ikhsan, Haerul (Universitas Negeri Surabaya, 2022)
This study aims to reveal what makes students not proficient in swimming courses. This research is a qualitative descriptive research with in-depth interview method. The population in this study were all 2nd semester students of the Sports Coaching Education Study Program who took part in the TP course contract. Swimming amounted to 58 students. The research sample was selected based on the Snowball Sampling technique, which had a sample of 8 students. The instrument in this study used an interview guide consisting of 10 questions about physical and psychological conditions during swimming courses. Result: Five students stated that their pulse was still normal. One student is sometimes normal, sometimes not. Two students stated that there was an increase in pulse rate. Five students stated that there was no problem with a history of injury. Three students stated that there are injuries that often recur. Seven students stated that there was no specific trauma in swimming. One student has a special trauma in swimming. Six students felt fine in their physical condition. One student did not know. One student felt his physical condition was not fine. All students did not feel nauseous during swimming courses. All research subjects felt difficulty in following the exemplified movements. Six students are interested in swimming lessons. Two students are not interested in swimming lessons, but want to be able to swim. Four students admitted that they did not feel restless in swimming lessons. Four students feel restless in swimming lessons. All research subjects feel worried and afraid of the depth of the water. All subjects feel happy in taking swimming courses. The conclusion is that sports students who are not proficient in swimming just need to be encouraged and motivated to be even more enthusiastic in learning swimming.